The Effect of Crop Residue Application to Soil Fauna Community and Mungbean Growth (Vigna radata) - SUGIYARTO SUGIYARTO (Biodiversitas Journal of Biological Diversity, 2000)
Litterbag experiment was carried out to determine the effect of crop residue application to soil fauna community andmungbean growth. The experiment arranged in randomized complete design with triplicate. The four treatment application of crotalarian, rice straw and banana’s aerial stem residues as well as without residue application as control. Soil fauna community and mungbean growth measured at 8 weeks after mungbean sown. Soil fauna extracted by modified Barless-Tullgren extractor apparatus. Height and dry weight of mungbean measured as crop growth parameters. The results indicated that the soil fauna densities and diversities as well as the growth of mungbean tended to increase by the application of crop residues. The effect of the treatment decreasing in thefollowing order: banana’s aerial stem residue > crotalarian residue > rice straw > without residue application. Therewere high correlation between mungbean growth and soil fauna diversities.© 2001 Jurusan Biologi FMIPA UNS Surakarta Key words: crop residue, soil fauna, mungbean.